UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA MATERI HIMPUNAN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Silmika Arfah; Haritsah Hammamah Harahap; Andi Saputra Mandopa (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2024)
This type of research is classroom action research. The research subject is SMP Negeri 9 Padangsidimpuan for the 2023/2024 academic year and the learning outcomes of students who are taught using the jigsaw type cooperative learning model. Based on the research results, it can be concluded that student learning outcomes on set material through the application of the jigsaw type cooperative learning model have achieved learning completeness. From the initial test results, it was found that the lowest score was 40 and the highest score was 80. 18 students got a score < 75, 60% of them and 12 students (40%) got a score ≥ 75 (requirement for learning completion). And the average score obtained in the initial test was 69. After giving action in cycle I two meetings and cycle II also two meetings through the stages of implementing the jigsaw type cooperative learning model at the end of the lesson to students, the average score was obtained -class average of 83.5. In the second learning outcomes test, it was seen that 26 students (86.67%) had completed their studies and 4 students (13.33%) had not completed their studies. By implementing the jigsaw type cooperative learning model, student learning outcomes in class VII-B SMP Negeri 9 Padangsidimpuan can be improved.